Inclusive research for agriculture development: farmers participation and innovation - Kumar, Arvind; Gupta RK; Jat, Mangi Lal; Malik, R.K.; Sidhu HS; Gopal R (2011)
Dissemination or extension of technologies among the farmers is a complex issue. More often than not the scientists, having developed and tested the technologies, are not able to transfer these to the farmers widely. W hy the farmer is not ready to adopt the new technology is an issue that haunts planners and scientists alike. Farmers today need a variety of information about protection, inputs & services (Van den Ban, 1998). Factors such as the size of landholding (Adhiguru et al. , 2009), production system of the farmers and availability of inputs and services affect the information needs of the farmers (Rivera, 1996; Farrington et al., 1997; Planning Commission, 2006). Agricultural extension must be seen as a wider concept, including agricultural and marketing skills, organizing farmers and other stakeholders, developing social capital, sustainable natural resource management and food and livelihood security (Swanson, 2008).